Successful Extracorporeal Life Support in a Case of Severe Glyphosate-Surfactant Intoxication. Issue 1 (January 2016) - Chan, Cheng-Wei; Wu, I-Lin; Lee, Ching-Hsing; Hsu, Shou-Chien; Liao, Shu-Chen
Abstract : Objective: To describe the experience of emergency extracorporeal membrane oxygenation in treating life-threatening glyphosate-surfactant intoxication. Design: Case report. Setting: Emergency department and ICU. Patient: A patient with cardiopulmonary failure after glyphosate-surfactant intoxication. Intervention: Extracorporeal membrane oxygenation. Case Report: A 47-year-old man presented with mildly decreased consciousness in our emergency department after ingesting approximately 100 mL of glyphosate-surfactant 1.5 hours previously. Respiratory failure, persistent ventricular tachycardia, profound shock refractory to inotropic agents, and metabolic acidosis developed in the patient within 2 hours. Extracorporeal membrane oxygenation was applied within 4 hours of cardiopulmonary failure. The patient's condition improved considerably. He was transferred to the general ward on the eighth day with stable hemodynamic status and complete neurological recovery. Conclusions: On the basis of our research, this was the first case in which extracorporeal membrane oxygenation was used to treat severe glyphosate-surfactant intoxication. We recommend early initiation of extracorporeal membrane oxygenation therapy to mitigate cardiopulmonary compromise in patients with glyphosate-surfactant intoxication.